THE MAIN PROVISIONS OF THE BOLOGNA PROCESS AND ITS RELEVANCE FOR UZBEKISTAN - Sherboeva , Nasimakhon (MMIT Proceedings, 2023)
The article is devoted to the Bologna process, its development and advantages. It is considered how the Bologna process affects the modern education system. The Bologna reform is aimed at creating a single European educational space, increasing the competitiveness of the European economy through changing the system of higher education. The author also examines which countries have implemented the Bologna system, as well as the issues of the implementation of the Bologna process in Uzbekistan.